Abuse elder and relationship life review (Journal Of Educational and Psychological Researches, 2022)
The study aimed at identifying the domains of abuse of the elderly (each field separately) of the research sample. The study sample consisted of (100) senior citizens residing in nursing homes in Baghdad and Kirkuk cities. They were selected in a simple random way. In order to achieve the research objectives, two scales were developed to measure the abuse of the elderly consisted of six domains: Neglection abuse, emotional abuse, physical abuse, social abuse, financial abuse, sexual abuse), and the other to measure the life review. The results showed that the level of abuse of older people in the sample is higher than the average in the society they belong to, the level of life review was higher than the average they belong to, and the areas of abuse of older people did not show any contribution to the review of life, The research came out with some recommendations and suggestions(Conducting a research and studies on abuse in the elderly and other psychological variables (such as depression, anxiety, conflict, aggression, etc).                 (Carrying out studies and treatment programs and guidance for the elderly).